Correcting Oral Errors for University Students (A classroom research in Bina Sarana Informatika University) - Mentari Pratami (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The objectives of the research are: 1). to make aware of the type of the students errors, 2). to develop positive strategies of error correction, 3). to find out the effective techniques in conducting errors correction, and 4). to know the students’ English progress after being corrected during the learning activity of the English Conversation II class in semester 4. The result of the research showed that most mistakes made by students consist of over generalization and interference errors. In correcting the errors, students prefer to have discussion, drilling, and echoing techniques. When the writer corrected errors, students gave good responses in terms of their willingness, and happiness.. The techniques of correcting errors applied by the writer have improved the students’ performance when they communicate in English. It was proved by the number of mistakes made by the students is 102. These mistakes were produced during their oral presentation in the last session of the class. The decreasing mistakes made by the students are from 192 to 102 mistakes. Due to the research findings, it is suggested to the teachers of English to do the error correction persistently otherwise, the mistakes became fossilized. Apply the right and effective techniques based on the students’ condition and personality. Make students participate actively in the learning activity by creating positive atmosphere so that students will feel free to express their thoughts in oral communication.